The Dual Role of a Reflective Future Teacher during School Practise - Krzeczkowska Małgorzata; Augustinovič Agata (Sciendo, 2024)
Introduction: Teaching and learning are processes that significantly impact one's future. Active participation in school practises serves as a strong foundation for future educators. This paper aims to present the viewpoints and feedback of university students on chemistry lessons conducted in schools by fellow university students as part of their training. The study explores how these prospective teachers perceive lessons while simultaneously playing the roles of both the teacher and an observer. It also investigates their ability to identify areas in need of support and those that require further development during their subsequent pre-service teacher training courses.